Increased PA2G4 Expression Is an Unfavorable Factor in Nasopharyngeal Carcinoma. Issue 7 (August 2021) - Xu, Yan; Cai, Hongbing; Tu, Wei; Ding, Lingying; Luo, Rongcheng
Abstract : PA2G4 plays a dual role in tumors. However, the correlation of its expression with clinical feature and prognosis has never been reported in nasopharyngeal carcinoma (NPC). Using immunohistochemical staining, we examined PA2G4 protein level in clinicopathologically characterized 201 NPC cases (138 male and 63 female) with age ranging from 21 to 83 years and 45 nasopharyngeal (NP) tissues. Statistical methods were used to assess the difference in PA2G4 expression and its relationship with clinical parameters and prognosis in NPC. Immunohistochemical analysis showed that the protein expression of PA2G4 examined in NPC tissues was higher than that in the nasopharyngeal tissues ( P =0.005). In addition, high levels of PA2G4 protein were positively correlated with tumor size (T classification) ( P <0.001), the status of lymph node metastasis (N classification) ( P <0.001), distant metastasis ( P =0.029), and clinical stage ( P <0.001) of NPC patients. Patients with higher PA2G4 expression had a significantly shorter overall survival time than did patients with low PA2G4 expression. Stratified analysis indicated that high expression of PA2G4 showed the inversed survival time in clinical stages III-IV, but not stages I-II. Finally, multivariate analysis suggested that the level of PA2G4 expression was an independent prognostic indicator ( P <0.001) for the survival of patients with NPC. Elevated protein expression of PA2G4 was significantly shown, which plays an unfavorable outcome for NPC patient survival.